2020
DOI: 10.1016/j.celrep.2020.107732
|View full text |Cite
|
Sign up to set email alerts
|

Variable Outcomes in Neural Differentiation of Human PSCs Arise from Intrinsic Differences in Developmental Signaling Pathways

Abstract: Highlights d Analysis of 162 iPSC neural differentiation quantifies sources of variability d Variation in outcomes occurs along developmental brain spatial and regional axes d Variation depends on iPSC-line-specific differences in Wnt/ b-catenin signaling d Effects of signaling differences can be rescued by exogenous pathway activation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 79 publications
9
48
0
Order By: Relevance
“…This variation is likely to have a major impact on cell fate decisions, as Wnt signaling is a key regulator of naive pluripotency, germ-layer specification ( Sato et al., 2004 ), and primitive endoderm differentiation ( Anderson et al., 2017 ). Interestingly, variations in Wnt signaling have also been shown to influence the differentiation behavior of human PSCs ( Blauwkamp et al., 2012 ; Strano et al., 2020 ). In agreement with this, we observed that naive hESCs also display different levels of Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This variation is likely to have a major impact on cell fate decisions, as Wnt signaling is a key regulator of naive pluripotency, germ-layer specification ( Sato et al., 2004 ), and primitive endoderm differentiation ( Anderson et al., 2017 ). Interestingly, variations in Wnt signaling have also been shown to influence the differentiation behavior of human PSCs ( Blauwkamp et al., 2012 ; Strano et al., 2020 ). In agreement with this, we observed that naive hESCs also display different levels of Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The low variance within donors suggests aspects of this lineage bias are under genetic control. These findings contribute a novel perspective on a growing body of research that is beginning to reveal the genetic origins of heterogeneity in transcription and differentiation potential of hPSCs (Bonder et al, 2021; Carcamo-Orive et al, 2017; Cuomo et al, 2020; DeBoever et al, 2017; Jerber et al, 2021; Kilpinen et al, 2017; Ortmann et al, 2020; Strano et al, 2020; Vigilante et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…Following the discovery of reprogramming factors (Takahashi and Yamanaka, 2006), functional heterogeneity in hiPSC differentiation potential has been a continuing focus of interest (Hu et al, 2010; Kanton et al, 2019; Mariani et al, 2015; Micali et al, 2020; Strano et al, 2020; Wang et al, 2020). Initial studies noted functional consequences of epigenetic memory of parental cell types in reprogrammed cells (Cahan and Daley, 2013; Kim et al, 2010; Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all stem cell lines have similar potency to generate organoids of a particular lineage as observed in the ability to generate retina, inner ear, and skin organoids from ESCs ( Lee et al., 2018 ; Osafune et al., 2008 ; Vƶlkner et al., 2016 ). Analysis of 162 differentiation strategies from 61 PSC lines identified Wnt/Ī² catenin signaling leads to the varied differentiation ability, and its activation could alleviate the outcomes ( Strano et al., 2020 ). Future strategies should focus on empirically investigating the organoid-forming efficiency for each ESC line before initiating functional studies.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%